2013
DOI: 10.1111/jfpe.12046
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Starch Processing Using Apparatus with Couette–Taylor Flow

Abstract: Couette-Taylor flow (CTF), which is characterized by the presence of Taylor vortices, ensures effective mixing, fast heat transfer and improved rheological properties of starch slurry. Therefore, this type of flow can be expected to provide favorable conditions for starch processing. In order to check how to intensify the process, starch gelatinization has been studied experimentally and using computer simulation in two CTF apparatuses of different volumes. The results show that, when the volume of apparatus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…Meanwhile, both amylose leaching and water absorption favored the increase in dissolved starch concentration (represented by ABS) in the continuous water phase in which starch granules were suspended. On the contrary, at T hj ≥ 85 C gelatinization can be completed (DSG = 1) even for higher values of starch slurry axial flow and values of ω lower than those investigated here (see Hubacz et al, 2013 andMasuda et al, 2013). When gelatinization is completed a pasting process starts and water absorption by starch granules (i.e.…”
Section: Properties Of Gelatinized Pastementioning
confidence: 76%
See 4 more Smart Citations
“…Meanwhile, both amylose leaching and water absorption favored the increase in dissolved starch concentration (represented by ABS) in the continuous water phase in which starch granules were suspended. On the contrary, at T hj ≥ 85 C gelatinization can be completed (DSG = 1) even for higher values of starch slurry axial flow and values of ω lower than those investigated here (see Hubacz et al, 2013 andMasuda et al, 2013). When gelatinization is completed a pasting process starts and water absorption by starch granules (i.e.…”
Section: Properties Of Gelatinized Pastementioning
confidence: 76%
“…The results from Hubacz et al (2013) revealed an increase in SGSD with increasing ω for ω < 11.56 rad/s and a reversed tendency for ω > 11.56 rad/s. Meanwhile, in the present experiments the impact of  on SGSD was difficult to evaluate for T hj ≤ 70ºC, while for T hj ≥ 85ºC the increase in SGSD with the increasing ω (without changing the tendency) was observed.…”
Section: Properties Of Gelatinized Pastementioning
confidence: 89%
See 3 more Smart Citations